Absence of the fourth cranial nerve in congenital Brown syndrome - Kaeser, Pierre-François; Rohde, Stefan; Kolling, Gerold (Acta ophthalmologica, 2012)
Abstract. Purpose: To elucidate the aetiology of congenital Brown syndrome. Methods: Four consecutive patients diagnosed with unilateral congenital Brown syndrome had a comprehensive standardized ocular motility examination. Any compensatory head posture was measured. Brain magnetic resonance imaging (MRI) with regard for the IV cranial nerve (CN) was performed in all patients. Orbital MRI was performed in 2/4 patients, with images acquired in eight directions of gaze and superior oblique (SO) muscle areas compared. Results: CN IV could not be identified bilaterally in two patients, but was absent only on the side of the Brown syndrome in the two other patients. On the normal side, orbital MRI revealed a smaller SO muscle area in upgaze than in downgaze, demonstrating normal actions of this muscle. On the side of the Brown syndrome, the SO area remained the same in upgaze and in downgaze and approximately symmetric to the area of SO in downgaze on the normal side. Conclusions: These cases add further anatomical support to the theory of paradoxical innervation in congenital Brown syndrome. CN IV was absent in two patients on the side of the Brown syndrome, but without muscle hypoplasia. SO muscle size did not vary in up- and downgaze, which we interpreted as a sign of constant innervation through branches of CN III.